Worsening renal function in patients hospitalized with acutely decompensated heart failure - Lazović, Marko; Radenković, Sonja; Stojanović, Dijana; Radović, Jelena; Stojanović, Miodrag; Tasić, Danijela; Stanojević, Dragana (Vojnosanitetski pregled, 2021)
Background/Aim. A predictor of a poor prognosis, renal dysfunction often manifests in patients with heart failure, and is associated with an increased mortality in these patients. The aim of the parent study was to determine risk factors associated with worsening renal function (WRF) in patients hospitalized for acutely decompensated heart failure. Methods. The study included 330 patients with acutely decompensated heart failure. Patients who developed WRF (n = 215, mean age 72.4 ± 9.8 years) were in the clinical group, and patients without WRF (n = 115, mean age 59.8 ± 11.7 years) were in the control group. Patients in the clinical group were observed according to: the age, gender, lipids, electrolytes, smoking, hypertension, and type of heart failure, with reduced or preserved left ventricle ejection fraction (HFrEF or HFpEF). We used logistic regression to calculate non-adjusted odds ratio (OR) and 95% confidence intervals for occurrence of WRF. Results. WRF was determined in 65.2% of patients with heart failure. Non-adjusted OR showed that there was a significant risk for development of WRF with age (OR = 4.3; p < 0.01), total cholesterol > 5.2 mmol/L (OR = 1.6; p < 0.05), hyponatremia 1.7 mmol/L, and gender, did not have any significance for the development of renal damage. Conclusion. Patients’ age, total cholesterol, hyponatremia, smoking, hypertension, and HFrEF were significant risk factors for worsening renal function in heart failure patients. Comparing predictive values, age could be the best prognostic tool for early identification of patients at risk for WRF.
Keywords: heart failure; cardio-renal syndrome; risk factors.